Load Balancing Optimization Analysis of 630 kVA Transformer to Reduce Neutral Current at KSBI Cirebon Substation - Diofany Nur Jamia; Taryo Taryo (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
Load imbalance in three-phase distribution transformers Load imbalance in three-phase distribution transformers can cause neutral current, increase power losses, reduce transformer efficiency, and disrupt the stability of the electricity distribution system. This study aims to analyze the effect of load balancing optimization on the reduction of neutral current in a 630 kVA distribution transformer at the KSBI Cirebon Substation. The method used is a quantitative method through measuring current and voltage on the secondary side of the transformer, calculating transformer loading, percentage of load imbalance, power losses, and transformer efficiency. In addition, simulations were carried out using ETAP 12.6.0 software with the unbalanced load flow method to compare conditions before and after load balancing. The results of the study show that under Peak Load Time (WBP) conditions, the load imbalance decreases from 15.71% to 5.86%, the calculated neutral current decreases from 41 A to 23 A, while the ETAP simulation results show a decrease in neutral current from 55 A to 19 A. Power losses under WBP conditions decrease from 2.244 kW to 2.165 kW, and the transformer efficiency increases from 97.78% to 97.84%. Under Off-Peak Load Time (LWBP) conditions, the load imbalance decreases from 12% to 3.19%, the calculated neutral current decreases from 36 A to 20 A, while the ETAP simulation results show a decrease in neutral current from 41 A to 20 A. Power losses under LWBP conditions decrease from 2.004 kW to 1.997 kW, and the transformer efficiency increases from 97.90% to 97.94%. Based on these results, it can be concluded that load balancing is effective in reducing neutral current, reducing power losses, and increasing the efficiency of distribution transformers at the KSBI Cirebon Substation.